Saturated fat and heart disease: The latest evidence. Issue 1 (15th January 2016) - Hruby, Adela; Hu, Frank B.
Abstract : In recent years, many nutrition news headlines exclaimed that saturated fat was not linked to heart disease, leaving the public confused about whether to limit intake, as has been the dietary recommendation for several decades. However, a more nuanced look at the evidence indicates that high saturated fat diets are in fact not benign with respect to heart disease risk. Dietary recommendations should emphasize replacing saturated fats typical in red and processed meats, and certain tropical oils and dairy forms, with healthier polyunsaturated and monounsaturated fat‐rich foods, such as nuts, olive oil, and fatty fish, as well as healthy sources of carbohydrates, such as fiber‐rich whole‐grain foods, rather than refined‐grain and sugar‐laden foods.